2017
DOI: 10.1017/s0960428617000361
|View full text |Cite
|
Sign up to set email alerts
|

Flora of Nam Kading National Protected Area Ii: 30 New Records of Angiosperms for Laos

Abstract: Thirty angiosperm species in 20 families, collected in Nam Kading National Protected Area, are recorded in Laos for the first time. Because the flora of Nam Kading is rich in endemic species, the area represents one of the core sites of plant biodiversity in Laos. To elucidate the plant diversity accurately, further intensive floristic surveys are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…This genus is mainly distributed from Nepal, China, India, Sri Lanka, Bangladesh, Myanmar, Thailand, Laos, Vietnam, throughout the Malesian region, and Australia (Swarupanandan et al, 1989;Forster, 1992;Li et al, 1995). Morphologically, they are terrestrial twining plants with milky latex, opposite leaves, axillary pseudo-umbelliform or raceme-like inflorescences, staminal corona with five lobes, with or without horned appendages, anther appendages, pentagonal stigma, pollinia with pellucid inner margins, single or paired follicles and winged seeds (Li et al, 1995;Jagtap & Singh, 1999, Thaithong et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This genus is mainly distributed from Nepal, China, India, Sri Lanka, Bangladesh, Myanmar, Thailand, Laos, Vietnam, throughout the Malesian region, and Australia (Swarupanandan et al, 1989;Forster, 1992;Li et al, 1995). Morphologically, they are terrestrial twining plants with milky latex, opposite leaves, axillary pseudo-umbelliform or raceme-like inflorescences, staminal corona with five lobes, with or without horned appendages, anther appendages, pentagonal stigma, pollinia with pellucid inner margins, single or paired follicles and winged seeds (Li et al, 1995;Jagtap & Singh, 1999, Thaithong et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…We found a Heterostemma specimen in the QBG herbarium from Phongsali province, northern Laos. After a careful examination of the specimen and consultation of the relevant literature (Lehmann et al, 2003;Callaghan, 2004;Newman et al, 2007aNewman et al, & 2007bInthakoun & Delang, 2008;Middleton, 2014;Prosperi et al, 2017;Park et al, 2018;Tagane et al, 2018), it was identified as Heterostemma succosum Kerr…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one flowering individual was found along a logging road. Despite repeated searches in the vicinity of the type locality for a total of ten days in 2016 and 2017 (Tagane et al, 2018), no other individuals were located. Given this situation, we consider the IUCN category of CR based on the Criterion D to be appropriate.…”
Section: Camellia Rosaceamentioning
confidence: 99%
“…While carrying out a series of botanical surveys in Laos in 2017 Tagane et al, 2017Tagane et al, & 2018Yang et al, 2018), we collected one Gentiana species from Phou Khao Khouay National Protected Area, central Laos characterized by a single erect stem and white corolla. After a careful examination using taxonomic literature (Ubolcholaket, 1987;Ho & Pringle, 1995;Ho & Liu, 2001;Ho, 2003;Hul, 2003Hul, & 2007, dried specimens deposited in herbaria (BKF, FOF, FU, HNL and KYO) and online digital specimen images (e.g.…”
Section: Introductionmentioning
confidence: 99%